G3BP1 regulates breast cancer cell proliferation and metastasis by modulating PKCζ - Liu, Shuang; Tian, Shaoping; Lin, Tianyu; He, Xin; Eze Ideozu, Justin; Wang, Rui; Wang, Yong; Yue, Dan; Geng, Hua (Frontiers in Genetics, 2022)
Breast cancer is a leading cause of death and morbidity among female cancers. Several factors, including hormone levels, lifestyle, and dysregulated RNA-binding proteins, have been associated with the development of breast cancer. Ras-GTPase-activating protein SH3 domain-binding protein 1 (G3BP1) and protein kinase C, Zeta isoform (PKCζ) are oncogenes implicated in numerous cancers, including breast cancers. However, their interaction and role in promoting breast cancer proliferation and metastasis have not been well-characterized. In the present study, we demonstrated that G3BP1 expression is elevated in breast cancer and that knockdown of G3BP1 diminished the proliferation and metastasis of breast cancer cells. Mechanistically, we identified a series of proliferating and metastasis-related properties, including chemotaxis, migration, Golgi polarity localization, and actin polymerization, that were modulated by G3BP1 knockdown. We found that G3BP1 and PKCζ co-localized and interacted intracellularly, and they co-underwent membrane translocation under EGF stimulation. Following the knockdown of G3BP1, we observed the membrane translocation and phosphorylation of PKCζ were significantly impaired, suggesting that G3BP1 regulates the activation of PKCζ. Our findings indicated that G3BP1 plays multiple roles in breast cancer cell proliferation and metastasis. The activation of PKCζ by G3BP1 may be the specific mechanism underlying the process.